Analisis Kebutuhan Pengembangan Lembar Kerja Peserta Didik Terintegrasi STEAM-PjBL tentang Materi Sistem Pencernaan untuk Peserta Didik Fase F - Zulyusri Zulyusri; Annisa Nurhidayah Putri (LP2M UIN Ambon, 2026)
Learning about the digestive system in Phase F still faces obstacles due to the complexity of the material and the conventional use of Student Worksheets. This study aims to analyze the need for developing integrated STEAM-PjBL Student Worksheets (LKPD) on digestive system material. The research method used is quantitative descriptive with one biology teacher and 39 students at SMA Negeri 7 Sijunjung as subjects. Data were collected through a needs questionnaire and analyzed using descriptive techniques. The results of the study indicate that students have difficulty understanding scientific terms and memorization-based material, while the available LKPDs have not integrated the STEAM-PjBL approach. The conclusion of the study states that the development of integrated STEAM-PjBL LKPDs is needed as a solution to create a contextual, interesting learning experience that is in line with the Merdeka Curriculum.